PERSEPSI KEGUNAAN, KEMUDAHAN PENGGUNAAN, DAN KENYAMANAN PENGARUHNYA TERHADAP NIAT DALAM MENGGUNAKAN APLIKASI MOBILE BANKING (Studi Pada Nasabah Perbankan Konvensional di Kota Palu) - Pratama, Adi; Saleh, Fadli Mohammad; Zahra, Femilia; Afdhalia, Nadhira (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Tadulako, 2019)
This research aims to evaluate and analyze the influence of perceived usefulness, ease of use, and convenience to intention to use mobile banking application. This type of research is survey research, using accidental method as sampling technique and obtained 60 respondent as the sample of research. The research method used in this study is quantitative research. Data analysis techniques using descriptive analysis and multiple linear regression using SPSS 21.0 program. The results shown that perceived usefulness, ease of use, and convenience has positive influence on intention to use mobile banking application.